Travestis brasileiras e exotismo sexual - Jorge Leite Jr (Ciências Sociais Unisinos)
Currently, Brazil seems to be fashion in the new global public sphere. This has apparently given a new global dimension to Brazil’s traditional image of being a generous and pacific country in which social conflicts are preferably settled within the scope of artistic creativity and sexual freedom. It is in this sense that the femininity of Brazilian trannies is able to enter the already vast field of the global imaginary on Brazilian eroticism. At the same time, this femininity is also able to tension many social difference markers (such as class, race/ethnicity and nationality) and to create for Brazilian trannies specific characteristics that are increasingly competitive in the transnational sex market.